Laporan Kasus Karsinoma Sel Skuamosa yang Berkembang dari Papiloma Tipe Inverted Sinonasal pada Pekerja Pabrik Cermin - Riani, Fety; Marlita Sari, Ita (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2022)
Background. Sinonasal inverted (PI) papilloma is a benign tumor of the mucosal epithelium of the nasal cavity and paranasal sinuses with an endophytic growth pattern. PI is more common in men in the fifth and sixth decades of life. These tumors have local aggressive behavior, high recurrence rates, and can undergo malignant transformation. Squamous cell carcinoma (SCC) is the most common malignancy developed from sinonasal PI. SSC developed from PI (KSS/PI) is related to exposure in the work environment. Methods. We report a sinonasal SCC/PI case by describing the clinical manifestations, radiological features, and histopathological features of a young male patient who was a non